Avaliação da mutagenicidade e da estrogenicidade dos extratos etanólicos padronizados, frações e substâncias isoladas de Arrabidaea brachypoda (DC.) Bureau - Nogueira, Catarine Haidê [UNESP] (2015)
The Arrabidaea brachypoda (DC.) Bureau, is a native of Cerrado shrub belonging to Bignoniaceae family, is known as vine-one or dyer and popularly used to treat arthritis. Several activity for this species have been recognized as an antifungal, antiviral, anti-inflammatory, antinocicepitivo effect and anti-Trypanosoma cruzi, but studies proving its effectiveness and safety are still rare, thus the objective since work was to evaluate the mutagenic activity through the Ames test and the estrogenic activity by testing recombinant yeast (RYA) of the extracts, fractions and compounds of A. brachypoda. The Ames Test was performed with Salmonella typhimurium strains TA100, TA98, TA97 and TA102, with and without metabolic activation by preincubation method. The RYA test was performed with Saccharomyces cerevisiae BY4741 strain with the extracts of the leaves, stalks, roots, their respective fractions and compounds. All the extracts and also the aqueous fraction of the leaves of A. brachypoda showed mutagenic activity and the extracts of leaves and roots also showed estrogenic activity. The results contribute to the knowledge about the safety of using this species, so we recommend caution with its use because the positive results regarding the mutagenicity and we believe that the risk of adverse effects by acting as endocrine changers is low.